2015
DOI: 10.5194/nhess-15-2069-2015
|View full text |Cite
|
Sign up to set email alerts
|

Recent trends in daily rainfall extremes over Montenegro (1951–2010)

Abstract: Abstract. More intense rainfall may cause a range of negative impacts upon society and the environment. In this study we analysed trends in extreme ETCCDI (Expert Team on Climate Change Detection and Indices) rainfall indices in Montenegro for the period between 1951 and 2010. Montenegro has been poorly studied in terms of rainfall extremes, yet it contains the wettest Mediterranean region known as Krivošije. Several indices of precipitation extremes were assessed including the number of dry days and rainfall … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
13
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 27 publications
8
13
0
2
Order By: Relevance
“…These global scale studies' findings were confirmed by numerous regional and local studies all over the world-in Asia (Sheikh et al, 2015), Africa (Ongoma, Chen, & Omony, 2018), America (Brown, Bradley, & Keimig, *Corresponding author, e-mail: tatjana.popov@pmf.unibl.org 2010; Skansi et al, 2013). Similar results were also obtained for Europe-at the continental level (Klein Tank & Können, 2003) and in its various regions-over the Iberian Peninsula (Bartolomeu, Carvalho, Marta-Almeida, Melo-Gonçalves, & Rocha, 2016), Apennine Peninsula (Boccolari & Malmusi, 2013), Balkan Peninsula (Burić, Luković, Bajat, Kilibarda, & Živković, 2015;Gajić-Čapka, Cindrić, & Pasarić, 2015;Kioutsioukis, Melas, & Zerefos, 2010;Malinović-Milićević, Mihailović, Radovanović, & Drešković, 2018;Unkašević & Tošić, 2011), Carpathian Basin (Bartholy & Pongrácz, 2007;Croitoru, Piticar, & Burada, 2016), Northern Europe (Lupikasza, Hansel, & Matschullat, 2011), etc. Although most of continentally averaged extreme precipitation indices (e.g., RX5day, R10mm, R20mm, R95p, and R95pTOT) have increased significantly since the mid-20th century, the observed trends were not spatially coherent (Klein Tank & Können, 2003).…”
Section: Introductionsupporting
confidence: 65%
“…These global scale studies' findings were confirmed by numerous regional and local studies all over the world-in Asia (Sheikh et al, 2015), Africa (Ongoma, Chen, & Omony, 2018), America (Brown, Bradley, & Keimig, *Corresponding author, e-mail: tatjana.popov@pmf.unibl.org 2010; Skansi et al, 2013). Similar results were also obtained for Europe-at the continental level (Klein Tank & Können, 2003) and in its various regions-over the Iberian Peninsula (Bartolomeu, Carvalho, Marta-Almeida, Melo-Gonçalves, & Rocha, 2016), Apennine Peninsula (Boccolari & Malmusi, 2013), Balkan Peninsula (Burić, Luković, Bajat, Kilibarda, & Živković, 2015;Gajić-Čapka, Cindrić, & Pasarić, 2015;Kioutsioukis, Melas, & Zerefos, 2010;Malinović-Milićević, Mihailović, Radovanović, & Drešković, 2018;Unkašević & Tošić, 2011), Carpathian Basin (Bartholy & Pongrácz, 2007;Croitoru, Piticar, & Burada, 2016), Northern Europe (Lupikasza, Hansel, & Matschullat, 2011), etc. Although most of continentally averaged extreme precipitation indices (e.g., RX5day, R10mm, R20mm, R95p, and R95pTOT) have increased significantly since the mid-20th century, the observed trends were not spatially coherent (Klein Tank & Können, 2003).…”
Section: Introductionsupporting
confidence: 65%
“…Their results have shown that the frequency of heavy rainfall has generally increased [21][22][23][24][25][26]. Specifically, the analysis of rainfall and extremes in Serbia has been the subject of several studies.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, the research on climate extremes has considerably progressed over the last few decades across the globe. Significant increases in extreme precipitation have been observed in western China, in the mid-lower reaches of the Yangtze River, and in parts of the southwest and south China coastal area [4], in India [5], in United States except for more easterly locations, particularly in South Carolina [6], in Bulgaria [7], in Germany [8], in France [9], in Brazil [10], and in south-western Montenegro [11]. In contrast, some regions show decreasing trends in extreme rainfall events especially in Kerala in India [12], in Poland [13], in South Asia and parts of the Central Pacific [14], in the north and east New Zealand [15], and in an ecological reserve in Federal District of Brazil [16].…”
Section: Introductionmentioning
confidence: 99%